Advanced Loop Thermosiphon With Check Valve (ALT/CV): Thermal Performance and Behavior - Booddachan, Khridsadakhon; Bhuwakietkumjohn, Nipon; Parameethanuwat, Thanya (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Nanofluids (NFs) are an attractive alternative to traditional working fluids for thermosiphons, but the solid nanoparticles (NPs) within the NF can agglomerate and reduce the thermal performance. This study focused on clarifying the effect of a NF with surfactants on the heat transfer characteristics of an advanced loop thermosiphon with a check valve (ALT/CV). In an experiment, the ALT/CV was filled with different working fluids at filling ratios of 30%, 50%, and 80% with respect to the evaporator volume. Heat was supplied at 20%, 40%, 60%, 80%, and 100% of the heater output (2000 W). Five working fluids were considered: deionized (DI) water, a DI water-based NF with 0.5 wt% silver NPs, and the same NF containing 0.5, 1, and 1.5 wt% oleic acid (OA) and potassium oleate (OAK+) as surfactants. The results showed that the ALT/CV provided a better heat transfer performance than a normal thermosiphon. The maximum heat transfer rate was achieved with the NF containing 0.5 wt% silver NPs and 1 wt% OAK+. The NF containing OAK+ demonstrated a heat transfer rate approximately 80% higher than that of the DI water